ANALISIS PERBANDINGAN RETURN DAN RISK SAHAM KONVENSIONAL DAN SYARIAH (Studi pada Jakarta Islamic Index (JII) dan IDX 30 Periode 2014-2018) - Rahma Putra, Ivan Yulian; Purbawati, Dinalestari (Jurnal Ilmu Administrasi Bisnis, 2020)
In 2016, JCI experienced the highest decline in the history of the Indonesia Stock Exchange, but in 2017 to 2018 it experienced a very high increase up to the point of 6,000, in that same year Islamic and conventional stock indexes experienced a volume increase of 167% for Islamic stocks and 130% for conventional shares. With an increase of this magnitude whether Islamic stocks show better profits than conventional stocks ,This research arranged to know the difference of average Return and Risk of sharia stock in Jakarta Islamic Index (JII) and conventional stock in IDX30 in the period 2014 until 2018. The type of this research is descriptive research with quantitative approach. The location of this research is the website of Indonesia Stock Exchange www.idx.co.id as a secondary dataâ€™s provider which provide issuerâ€™s names included in JII and IDX30 and closing price of monthly stock period 2014 until 2018. Data analysis technique used in this research is descriptive and inferential statistic analysis. The results of descriptive analysis within 5 years showed that the average return of sharia stock is 0,185328952 or 18.5% while the average return of conventional stock is 0,174286182 or 17,42%. The Risk level of Sharia stock fora period of 5 years is 0,04180884 or 4,1% while the level of risk of conventional stock is 0,047664339 or 4,76%. Based on the results of inferential analysis by using different test (Independent Sample t-test) obtained result that there is no significant difference between return and risk of sharia stock with conventional stock.Â